2014
DOI: 10.1128/cvi.00115-14
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bactericidal Assays To Evaluate Typhoidal and Nontyphoidal Salmonella Vaccines

Abstract: Invasive Salmonella infections for which improved or new vaccines are being developed include enteric fever caused by Salmonella enterica serovars Typhi, Paratyphi A, and Paratyphi B and sepsis and meningitis in young children in sub-Saharan Africa caused by nontyphoidal Salmonella (NTS) serovars, particularly S. enterica serovars Typhimurium and Enteritidis. Assays are needed to measure functional antibodies elicited by the new vaccines to assess their immunogenicities and potential protective capacities. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 48 publications
2
53
0
Order By: Relevance
“…In the absence of HL-60 cells, there was no detectable bacterial killing. Thus, at a concentration of 12.5%, BRC was unable to mediate killing, as shown previously (16). When HL-60 cells were incubated with bacteria and serum without BRC, limited OPA titers were observed for immune mice (1:400) but not for nonimmune mice.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…In the absence of HL-60 cells, there was no detectable bacterial killing. Thus, at a concentration of 12.5%, BRC was unable to mediate killing, as shown previously (16). When HL-60 cells were incubated with bacteria and serum without BRC, limited OPA titers were observed for immune mice (1:400) but not for nonimmune mice.…”
supporting
confidence: 76%
“…We previously developed a complementdependent serum bactericidal antibody (SBA) activity assay that quantifies serum antibody responses to typhoidal (S. Typhi and S. Paratyphi A) and nontyphoidal (S. Typhimurium and S. Enteritidis) Salmonella (16). Here, we describe an assay that measures the opsonophagocytic capacity of NTS antibodies based on the wellcharacterized pneumococcus opsonophagocytic activity (OPA), which employs HL-60 phagocytic cells and a standardized source of complement, i.e., baby rabbit complement (BRC) (17,18).…”
mentioning
confidence: 99%
“…Typhimurium (Lindberg ), expresses almost entirely short‐chain OPS (Boyd et al . ). We found that expression of wzzB from S .…”
Section: Discussionmentioning
confidence: 97%
“…SBA. The serum bactericidal assay (SBA) was performed as previously described (57). In brief, log-phase cultures (optical density at 600 nm [OD 600 ], 0.5 at 37°C) of S. Typhi strain Ty2 were prepared in Luria-Bertani (LB) broth with 10 mM NaCl.…”
Section: Methodsmentioning
confidence: 99%